The Initiation, but Not the Persistence, of Experimental Spondyloarthritis Is Dependent on Interleukin-23 Signaling - van Tok, Melissa N.; Na, Songqing; Lao, Christopher R.; Alvi, Marina; Pots, Desirée; van de Sande, Marleen G. H.; Taurog, Joel D.; Sedgwick, Jonathon D.; Baeten, Dominique L.; van Duivenvoorde, Leonie M. (Frontiers in Immunology, 2018)
IL-17A is a central driver of spondyloarthritis, its production was originally proposed to be IL-23 dependent. Emerging preclinical and clinical evidence suggests, however, that IL-17A and IL-23 have a partially overlapping but distinct biology. We aimed to assess the extent to which IL-17A-driven pathology is IL-23 dependent in experimental spondyloarthritis. Experimental spondyloarthritis was induced in HLA-B27/Huβ2m transgenic rats, followed by prophylactic or therapeutic treatment with an anti-IL23R antibody or vehicle control. Spondylitis and arthritis were scored clinically and hind limb swelling was measured. Draining lymph node cytokine expression levels were analyzed directly ex vivo, and IL-17A protein was measured upon restimulation with PMA/ionomycin. Prophylactic treatment with anti-IL23R completely protected against the development of both spondylitis and arthritis, while vehicle treated controls did develop spondylitis and arthritis. In a therapeutic study, anti-IL23R treatment failed to reduce the incidence or decrease the severity of experimental spondyloarthritis. Mechanistically, expression of downstream effector cytokines, including IL-17A and IL-22, was significantly suppressed in anti-IL23R versus vehicle treated rats in the prophylactic experiments. Accordingly, the production of IL-17A upon restimulation was reduced. In contrast, there was no difference in IL-17A and IL-22 expression after therapeutic anti-IL23R treatment. Targeting the IL-23 axis during the initiation phase of experimental spondyloarthritis– but not in established disease –inhibits IL-17A expression and suppresses disease, suggesting the existence of IL-23 independent IL-17A production. Whether IL-17A can be produced independent of IL-23 in human spondyloarthritis remains to be established.